Incidentally diagnosed type 2 youssef's syndrome with migrated postcesarean postpartum intrauterine contraceptive device - Vibha Mishra; Himanshu Pandey; Shashank Shekhar; Charu Sharma (Wolters Kluwer Medknow Publications, 2022)
Vesicouterine fistula (VUF) also called Youssef's syndrome is a rare and the least commonly encountered entity among genitourinary fistulae. Treatment options range from excision of the fistulous tract with hysterectomy and primary closure of the urinary bladder to fistula repair. Migrated postpartum intrauterine contraceptive device is one of the rarest causes for VUF. Here, we are describing a case of incidentally diagnosed VUF with Type 2 Youssef's syndrome with migrated postplacental (postcesarean) intrauterine contraceptive device, treated with uterus-sparing laparoscopic VUF closure.